An Optimized method of thermoelectric cooler-based thermal management for improving the luminous efficacy of light-emitting diodes - Nguyen, Quang-Khoi (Photonics Letters of Poland, 2024)
We experimentally performed a method of active cooling for white LED that can reduce the temperature of the LED by using TEC for reducing the temperature of the LED board. The relation of LED board and input power for TEC was investigated to find out the optimized curve of LED board temperature and input power for TEC. Also, the TEC based cooling system was applied for RGBW LEDs. The obtained result is meaningful in LED thermal management, improving the lighting quality and increases the lifespan for both middle and high-power LED types. Full Text: PDF References E.F. Schubert, J.K. Kim, "Solid-State Light Sources Getting Smart", Science, 308, 1274 ¬(2005). CrossRef Q.K. Nguyen, "Emission spectrum modeling of white LEDs light source with using Gaussian function", Photonics Lett. Pol.,15(4), 54 (2023). CrossRef C.C. Sun, S.H. Ma, Q.K. Nguyen, "Advanced LED Solid-State Lighting Optics", Crystals, 10, 758 (2020). CrossRef S.P. Ying, H.K. Fu, W.F. Tang, R.C. Hong, "The Study of Thermal Resistance Deviation of High-Power LEDs", IEEE Trans. Electron Devices, 61, 2843 (2014). CrossRef K. Górecki, P. Ptak, "Compact Modelling of Electrical, Optical and Thermal Properties of Multi-Colour Power LEDs Operating on a Common PCB", Energies, 14, 1286 (2021). CrossRef C.C. Sun, Q.K. Nguyen, T.X. Lee, S.K. Lin, C.S. Wu, T.H. Yang, Y.W.Yu. "Active thermal-fuse for stopping blue light leakage of white light-emitting diodes driven by constant current", Sci. Rep. 12, 12433 (2022). CrossRef Q.K. Nguyen, B. Glorieux, G. Sebe , T.H. Yang, Y.W. Yu , C.C. Sun, "Passive anti-leakage of blue light for phosphor-converted white LEDs with crystal nanocellulose materials", Sci Rep. 13, 13039 (2023). CrossRef N. Bădălan (Drăghici), P. Svasta, C. Marghescu, "A Method for Improving an Active Cooling Solution for LEDs ", IEEE 24th International Symposium for Design and Technology in Electronic Packaging (SIITME), Iași, Romania (2018). CrossRef A. Fan, R. Bonner, S. Sharratt, Y.S. Ju, "An innovative passive cooling method for high performance light-emitting diodes", 28th Annual IEEE Semiconductor Thermal Measurement and Management Symposium (SEMI-THERM), 319-324 (2012). CrossRef D.W. Kim, E. Rahim, A. Bar-Cohen, B. Han, "Direct Submount Cooling of High-Power LEDs", Compon. Packag. Technol., 33, 698 (2010). CrossRef N. Guan, N. Amador-Mendez, A. Kunti, A. Babichev, S. Das, A. Kapoor, N. Gogneau, J. Eymery, F.H. Julien, C. Durand, M. Tchernycheva, "Heat Dissipation in Flexible Nitride Nanowire Light-Emitting Diodes", Nanomater, 10, 2271 (2020). CrossRef S. Li, J.L. Liu, L. Ding, J.X. Liu, J. Xu, Y. Peng, M.X. Chen, "Active Thermal Management of High-Power LED Through Chip on Thermoelectric Cooler", IEEE Trans. Electron Devices, 68, 1753 (2021). CrossRef G.R. Sui, J.J. Chen, H. Ni, Y.Y. Ma, X.M. Gao, N. Wang, "Improvement of LED Performance With an Integrated Thermoelectric Cooling Package", IEEE Access, 8, 116535 (2020). CrossRef